Evaluation of the Oxo-bridged Dinuclear Ruthenium Ammine Complex as Redox Mediator in an Electrochemical Biosensor - Raymundo-Pereira, Paulo A. [UNESP]; Mascarenhas, Ana C. V. [UNESP]; Teixeira, Marcos F. S. [UNESP] (Wiley, 2016)
The mediation of electron-transfer by oxo-bridged dinuclear ruthenium ammine [(bpy)2(NH3)RuIII(μ-O)RuIII(NH3)(bpy)2]4+ for the oxidation of glucose was investigated by cyclic voltammetry. These ruthenium (III) complexes exhibit appropriate redox potentials of 0.131-0.09V vs. SCE to act as electron-transfer mediators. The plot of anodic current vs. the glucose concentration was linear in the concentration range between 2.52×10-5 and 1.00×10-4molL-1. Moreover, the apparent Michaelis-Menten kinetic (KM app) and the catalytic (Kcat) constants were 8.757×10-6molL-1 and 1,956s-1, respectively, demonstrating the efficiency of the ruthenium dinuclear oxo-complex [(bpy)2(NH3)RuIII(μ-O)RuIII(NH3)(bpy)2]4+ as mediator of redox electron-transfer.
Keywords: Electrochemical Biosensor; Electron Transfer; Glucose Oxidase (Aspergillus niger); Oxo-bridged dinuclear ruthenium ammine complex; Redox Mediator